Dimensionamento dos elementos da superestrutura de uma ponte em arco triarticulado de madeira sob a ótica do projeto de revisão da NBR 7190 de 2011 - Brito, Eder Leite de (2013)
Of great importance to the development of municipalities in the State of Mato Grosso, from economic and social point of view, the roads must ensure the entry of inputs in agricultural properties, the output of the production and the free movement of rural populations. However, it should be noted that, over the years, incorrect processes of construction and maintenance were employed in these ways, mainly by absence of technical information from State and Municipal Administrations. On this reality, the work has as its main objective to verify if the sections of elements of the superstructure of a glulam arch bridge, with up road deck, are usual, both of lumber, as Glulam, and if it is possible to establish a simplified roadmap to design the superstructure elements of this bridge, considering the criteria set out by the NBR 7190 project review, from ABNT (2011). As a parameter to the bridge design, was adopted, as a reference, the geometrical characteristics of the bridge over the Rio Claro in the city of Cuiabá – MT. As a conclusion it was found that the design can be simplified, because the curves of maximum efforts obtained define the format and the position of the maximum values, providing directly the design maximum values. It was concluded too that all elements of the bridge, built of lumber, have commercial dimensions easily found in sawmills of Mato Grosso. In addition, it was noted that the dimensions obtained for the laminated arch of this bridge, as well as its metallic elements, are easy to manufacture by the Brazilian industry, what makes this bridge model quite feasible under the technical point of view.